Factors associated with bariatric surgery rates in federative units in Brazil - Ivan Augusto Cecilio e Silva; Cassia Kely Favoretto; Leticia Xander Russo (Revista de Saúde Pública, 2022)
OBJECTIVE: To analyze the socioeconomic, demographic and health management factors associated with bariatric surgery rates performed by the Brazilian Unified Health System (SUS) in the federative units in Brazil. METHODS: Description and analysis of bariatric surgeries rates (per 100,000 inhabitants) performed by SUS in adults from 18 to 65 years old, in the 27 federative units of Brazil, between 2008 and 2018; thus, the econometric methodology of count panel with negative binomial distribution (population-averaged, fixed effects and random effects) was used. Socioeconomic and demographic factors were also investigated, considering the real gross domestic product per capita, the average years of study of adults and life expectancy at birth, and those of health management, given the primary health care coverage, the rate of digestive system surgeons and the rate of hospitals accredited in high complexity care to patients with obesity in the SUS. RESULTS: In regional terms, the performance of public bariatric surgeries in Brazil over the period analyzed suffered a great disparity; the procedures happen mostly in the South and Southeast regions, and scarcely in the North region. Moreover, we found a positive relationship between the rate of bariatric surgeries and life expectancy, the rate of digestive system surgeons and the rate of hospitals accredited in high complexity care; however, the average number of years of adult study and coverage of primary health care is a negative association regarding real gross domestic product per capita. CONCLUSION: In the period analyzed, the investigated factors explained the rate of bariatric surgeries. Therefore, to train specialized health professionals, the accreditation of hospitals according to the legal framework, preventive actions of primary care, and socioeconomic and demographic factors, conditioning for the offer of surgical treatment by the SUS were crucial. Thus, these are all relevant factors for the formulation of public policies in this area. – – OBJETIVO: Analisar os fatores socioeconômicos, demográficos e de gest\~ao em saúde associados às taxas de cirurgias bariátricas realizadas pelo Sistema Único de Saúde (SUS) nas unidades federativas (UF) do Brasil. MÉTODOS: Descriç\~ao e análise da taxa de cirurgias bariátricas (por 100 mil habitantes) realizadas pelo SUS em adultos de 18 a 65 anos, nas 27 unidades federativas do Brasil, entre 2008 e 2018; para isso, utilizou-se a metodologia econométrica de painel de contagem com distribuiç\~ao binomial negativa (population-averaged, efeitos fixos e efeitos aleatórios). Investigou-se, também, os fatores socioeconômicos e demográficos, considerando o produto interno bruto (PIB) real per capita, a média de anos de estudo de adultos e a expectativa de vida ao nascer, e os da gest\~ao em saúde, tendo em vista a cobertura da atenç\~ao básica, a taxa de cirurgi\~oes de aparelho digestivo e a taxa de hospitais credenciados na assistência de alta complexidade (AAC) ao indivíduo obeso no SUS. RESULTADOS: Em termos regionais, verificou-se grande disparidade na realizaç\~ao de cirurgias bariátricas públicas no Brasil ao longo do período analisado: os procedimentos est\~ao concentrados nas regi\~oes Sul e Sudeste, sendo escassos na regi\~ao Norte. Além disso, encontrou-se uma relaç\~ao positiva entre a taxa de cirurgias bariátricas e a expectativa de vida, a taxa de cirurgi\~oes de aparelho digestivo e a taxa de hospitais credenciados na assistência de alta complexidade; havendo, porém, uma associaç\~ao negativa em relaç\~ao ao PIB real per capita, a média de anos de estudo de adultos e a cobertura da atenç\~ao básica. CONCLUS\~OES: No período analisado, o índice de cirurgias bariátricas foi explicado pelos fatores investigados. Portanto, mostrou-se de fundamental importância a formaç\~ao de profissionais de saúde especializados, o credenciamento de hospitais conforme o marco legal, as aç\~oes preventivas da atenç\~ao básica, e os fatores socioeconômicos e demográficos, condicionantes da oferta do tratamento cirúrgico pelo Sistema Único de Saúde. Sendo assim, todos fatores relevantes para a formulaç\~ao de políticas públicas nessa área.
Keywords: I1; C01; 330; Bariatric Surgery; Healthcare Disparities; Sociodemographic Factors.; Socioeconomic Factors